THE EFFECT OF Spirulina sp FLOUR FORTIFICATION ON THE SENSORY-CHEMICAL CHARACTERS OF MOCHICAKE - Hagairim Sagala; Mirna Ilza; Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The aim of the study was to observe the effect of Spirulina flour fortifiedto the mochi cake on its sensory-chemical characters This study used anexperimental method by using completely randomized design (CRD) nonfactorial. The treatment conducted was producing mochi cake by adding Spirulinaflour at different composition, namely: 1.5, 2.5, and 3.5gs for 1120 gs mochi each.The products of Mochi cake fortified with the Spirulina flour were evaluated fortheir hedonic value and chemical characters. The result showed that thefortification of 3,5gs Spirulina flour into the mochi was determined as the besttreatment indicated by the highest value of appearance 7.4, texture 7.0, aroma 6.9,and taste 7.7. The product was containing water 28.50%, protein 3.20%, 4.60 fat,ash 3.62% and carbohydrate 60.08%.Keywords: fortification, mochi cake, Spirulina flour